Influence of The Ratio of Profit Margin, Financial Leverage Ratio, Current Ratio, Quick Ratio Against The Conditions and Financial Distress - Andi Purnomo (Indonesian Journal of Business, Accounting and Management (IJBAM), 2018)
Financial distress is occurred before bankruptcy. This condition could be predicted by analyzing Financial Statement. This study aims to determine whether there is significant influence between profit margin ratio, financial leverage ratio, current ratio, and quick ratio on Financial distress to determine how much their influeance on Financial distress in a Company. Based on result of data processing using SPSS 17.0 version, the author obtained value of multiple correlation coeffiicient in 2008 is 0.933 (R), it means X1 (profit margin ratio), X2 (financial leverage ratio), X3 (current ratio) and X4 (quick ratio) jointly have strong and positive relationship in predicting Financial distress, And for value of multiple correlation coefficient in 2009, obtained 0.582 (R), it means X1 (profit margin ratio), X2 (financial leverage ratio), X3 (current ratio) and X4 (quick ratio) jointly have strong and positive relationship in predicting Financial distress. Based on F-test calculation in 2008, multiple linear regression is obtained that Fhitung > Ftable. Value of Fhitung is 40,962, whereas value of Ftable is 2,922, it means that Ha is rejected and Ho is accepted. This means regression model can be used to predict financial distress condition or it can be said that X1 (profit margin ratio), X2 (financial leverage ratio), X3 (current ratio) and X4 (quick ratio) jointly influence significanly on Company’s Financial Statement condition (Y). whereas for F-test calculation in 2009, multiple linear regression is obtained that Fhitung > Ftable , value of Fhitung is 13,839 and value of Ftable is 2,922. it means that Ha is rejected and Ho is accepted. This means regression model can be used to predict financial distress condition or it can be said that X1 (profit margin ratio), X2 (financial leverage ratio), X3 (current ratio) and X4 (quick ratio) jointly influence significantly on Company’s Financial Statement condition (Y).